Urdimbrar. Las violencias en la comunidad LGBTIQ+ en el marco del informe final de la CEV desde una perspectiva ética de la representación escénica (2023)
This document marks the epistemological basis that support the theatre play Urdimbrar, taking a discussion about the theatre making methodology in relation with its contents. The objective of this research is to make a stage play framed in performatic theatre, from an analysis of LGBTIQ+ victims of violences within the Comisión para el Esclarecimiento de la Verdad, la Convivencia y la No Repetición [CEV] Final Report, from an ethic perspective of stage representation. Methodologically, was used the research+making as it is understood as masking new knowledge from artistic processes.